BRCA1, BRCA2 mutations - future of predictive oncology: a review of literature - V. N. Dmitriev; I. V. Sukhoterin; I. I. Zybenko; T. V. Dmitrieva (ABV-press, 2014)
In recent years, it has been demonstrated that breast cancer arising in BRCA1 and BRCA2 mutation carriers differs in its morphological, immuno- phenotypic and molecular characteristics from sporadic breast cancer. In addition to improving our understanding of the biology of hereditary breast cancer, the recognition of these differences could also be used to predict BRCA mutation status in a given group of patients.